2007
DOI: 10.1007/s10029-007-0315-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled, blinded trial of Tissucol/Tisseel for mesh fixation in patients undergoing Lichtenstein technique for primary inguinal hernia repair: rationale and study design of the TIMELI trial

Abstract: TIMELI is a major international trial that will provide important information on the efficacy and safety of Tissucol, compared with sutures, for mesh fixation in patients undergoing Lichtenstein technique for primary inguinal hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
5
32
0
1
Order By: Relevance
“…The application of autologous P-RFS was feasible in all procedures. The mean volume of sealant we applied was comparable to previously reported volumes of normal fibrin sealants [4,5] . An absorbable stay suture was used twice after hernia sac reduction.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The application of autologous P-RFS was feasible in all procedures. The mean volume of sealant we applied was comparable to previously reported volumes of normal fibrin sealants [4,5] . An absorbable stay suture was used twice after hernia sac reduction.…”
Section: Discussionsupporting
confidence: 71%
“…Nowadays, most of the commonly used sealants contain human or bovine components. Small trials using these sealants have shown promising results and were the reason for a large international randomized trial [4,5,16,17] . The incidence of pathogen transmission with these glues is very low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in various hernia repairs both open and laparoscopic using fibrin glue have shown promising results. 8,9 This is further authenticated by our study.…”
Section: Mechanism Of Actionsupporting
confidence: 71%
“…Generally, sutures are generally used to secure the prosthetic mesh; however, that may lead to chronic pain and other problems such as numbness or groin discomfort, presumably through tension or nerve compression [5]. Some studies showed that chronic pain was influenced by the type of the mesh implanted and its fixation [22,23]. For these reasons, some surgeons searched for a new type of atraumatic methods of fixation.…”
Section: Discussionmentioning
confidence: 99%